Cosmological considerations on the general theory of relativity - Einstein, Albert (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2017)
A. Einstein, “Kosmologische Betrachtungen zur allgemeinen Relativitätstheorie” (“Cosmological considerations on the general theory of relativity”), Sitzung der Physikalisch-mathematischen Klasse vom 8. Februar 1917, „Sitzungsberichte der Preußischen Akad. d. Wissenschaften, 1917”, pp. 142–152. Translated to Polish from original German work by Robert Janusz.